ChemInform Abstract: Antiinflammatory Sesquiterpenes from the Medicinal Herb Tanacetum sinaicum. Issue 41 (October 2015) - Hegazy, Mohamed‐Elamir F.; Hamed, Ahmed R.; Mohamed, Tarik A.; Debbab, Abdessamad; Nakamura, Seikou; Matsuda, Hisashi; Pare, Paul W.
Abstract From newly isolated sesquiterpenes (I), (II), and (III) only (I) shows intermediate inhibition of NO production in a mouse peritoneal macrophage system (IC50: 15.7 μM).